NUTRITIONAL AND SENSORY EVALUATION OF CONVECTIVE DRIED FRUTI - Giordan, Barbara Helen; Alchieri, Moara; de Souza, Edson Luiz; Soares, Fabiana Andreia A. S. M. (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
Most vegetables and fruits are highly perishable due to a high water content, which makes it difficult to trade, since seasonality and distance between markets demand costly refrigerated storage and transportation. Increasing shelf life and availability throughout the year by processing reduces losses by marketing of fresh foods. The drying or dehydration is a technique used from the antiquity for the conservation of foods, once the water affects in a decisive way the time of preservation of the products, influencing his/her quality and durability directly. The objectives of the present work were to assess the nutritional quality and conduct consumer sensory evaluation testing of convective dried fruits. They were processed apple, bananas, papaya, melon, kiwi and pear. Convective drying was carried out in the dryer a tray cabinet at 60 C and 1.25 m.s-1 to obtain a product with 15% moisture content.  Dehydrated fruits were evaluated for their physicochemical and microbiological characteristics. The sensorial attributes were appraised for 30 consumers using climbs hedonic of five points. The results showed that the convective drying maintained the nutritional quality of the fruit when compared to the fresh product. Sensory analysis showed that the product obtained high acceptance rate, corresponding to the second and third levels of hedonic scale (liked and enjoyed regularly). The feature that predominantly influenced acceptance of the product was the appearance, flavor and aroma. The texture was the attribute that less influenced the acceptance.